Evaluation of anastomosis canal in maxillary sinus walls using cbct in South Indian population: A cross-sectional study - A Shiny; Jaishankar P Hombarvali; Karthikeya Patil (Wolters Kluwer Medknow Publications, 2023)
Background: Intraosseous anastomosis (IA) found in the lateral wall of the maxillary sinus (MS) is a potential site for bleeding during surgeries. Objectives: To investigate the position of IA in male and female, and dentulous and edentulous patients in relation to the MS floor and volume of MS. Methods: The study is comprised of 60 cone-beam computed tomography (CBCT) scans of the maxilla. Distances from the floor of the MS to the IA canal and from the MS floor to the alveolar crest were measured. The canals are classified into three types. The volume of the MS and its relation to the IA was assessed. Results: Statistical difference was noted in the position of the IA in relation to second premolar and in dentulous and edentulous patients. Intraosseous was the most common type of canal. The difference in volume did not affect the position of the canal. Conclusions: IA was closer to the floor of the MS in the second premolar region in females. Knowing the type and position of the canal helps prevent complications during surgery.